ANALISIS PEMANFAATAN MEDIA PEMBELAJARAN DI SD NEGERI 1 PATUKANGAN - Nur Laili Maulida; Prasena Arisyanto; Sukamto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The position of learning media is a crucial element in learning. Teachers at Patukangan 1 Public Elementary School have utilized media in learning that is relevant to the content they teach. The research objective to be achieved is to determine the use of learning media at Patukangan 1 Public Elementary School along with the obstacles and efforts encountered in learning. The type of research used in this study is descriptive qualitative. Data collection techniques used interview methods, observation, questionnaires, and documentation, while for data analysis using data reduction, data presentation, and data verification steps. The results obtained from the study showed that classroom teachers utilize media in the learning process such as concrete objects, models, multimedia media, and print media. Students are involved in learning with the presence of media, where students find it easier to understand the subject matter and feel interested in participating in learning. However, there are obstacles in the implementation of teaching activities, namely limited resources, limited time, and technical constraints. Even so, teachers can provide alternative solutions to overcome these obstacles, including teachers creating their own media, teachers making more structured learning devices, and teachers finding replacement projectors and laptops. Teachers utilize various media in learning that increase students' understanding and interest, even though they face obstacles that can be overcome with creative solutions.